2022
DOI: 10.3390/antiox11010115
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid Biosynthetic Gene SlCYP90B3 Alleviates Chilling Injury of Tomato (Solanum lycopersicum) Fruits during Cold Storage

Abstract: Tomato is susceptible to chilling injury during cold storage. In this study, we found that low temperature promoted the expression of brassinosteroid (BR) biosynthetic genes in tomato fruits. The overexpression of SlCYP90B3 (SlCYP90B3-OE), a key BR biosynthetic gene, alleviated the chilling injury with decreased electrical conductivity and malondialdehyde. In SlCYP90B3-OE tomato fruits, the activities of antioxidant enzymes, including ascorbate peroxidase (APX), catalase (CAT), peroxidase (POD), and superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The same mechanism also was reported in a recent investigation that the overexpression of the CPD gene involved in C-3 oxidase of the BR biosynthesis pathway significantly elevated the activities of antioxidant enzymes (SOD, POD, CAT, GR, and APX) to resist oxidative injury under drought stress (Zhou et al, 2016 ). When fruits were exposed to cold storage conditions, the SlCYP90B3 gene, which participates in the early stage of the C-22 α-hydroxylation in BR biosynthesis, increased the chilling tolerance of fruits through aggrandizing antioxidant system (Hu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same mechanism also was reported in a recent investigation that the overexpression of the CPD gene involved in C-3 oxidase of the BR biosynthesis pathway significantly elevated the activities of antioxidant enzymes (SOD, POD, CAT, GR, and APX) to resist oxidative injury under drought stress (Zhou et al, 2016 ). When fruits were exposed to cold storage conditions, the SlCYP90B3 gene, which participates in the early stage of the C-22 α-hydroxylation in BR biosynthesis, increased the chilling tolerance of fruits through aggrandizing antioxidant system (Hu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that BR is involved in the endogenous response to toleration of postharvest CI by increasing the synthesis of enzymes and antioxidant molecules, inhibiting protein degradation, and maintaining cellular energy status through signaling cascades with other hormones, which generates a reduction in the CI of the fruit [48,49]. In our experiment, the fruits with immersion in BR, regardless of the analogue, presented increased antioxidant activity (ABTS and DPPH radicals) and total phenol content (TPC) (Figure 5).…”
Section: Discussionmentioning
confidence: 99%